2021
DOI: 10.1122/8.0000262
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing thixotropy from viscoelasticity

Abstract: Owing to non-linear viscoelasticity, materials often show characteristic features that resemble those of thixotropy. This issue has been debated in the literature over the past several decades, and several experimental protocols have been proposed to distinguish thixotropy from viscoelasticity. In this work, we assess these protocols by carrying out experiments using polymer solutions, thixotropic clay dispersions and modelling their behavior respectively using the FENE-P constitutive equation and a viscoelast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…step-down in shear rate, and the same is true for the step-up test. This results in an indistinguishable stress response for thixotropic, anti-thixotropic and viscoelastic materials 47 .…”
Section: Introductionmentioning
confidence: 99%
“…step-down in shear rate, and the same is true for the step-up test. This results in an indistinguishable stress response for thixotropic, anti-thixotropic and viscoelastic materials 47 .…”
Section: Introductionmentioning
confidence: 99%
“…Formally, “pure” thixotropy is observed if a time-dependent viscous stress only takes place with stress relaxation or recovery (elastic) strain [ 26 ]. One can find a detailed discussion concerning the difference between thixotropy and other time-dependent processes in [ 27 , 28 ].…”
Section: Thixotropy—the Most Evident Reflection Of Structure Transfor...mentioning
confidence: 99%
“…In this review, we do not list a great number of experimental studies because one can find many references in publications [ 26 , 27 , 28 , 29 , 30 , 31 , 34 , 36 , 44 ], thus, there is no sense in repeating them here. The flood of studies of thixotropic behavior in various technological liquids continues, due to the necessity to classify and standardize these objects.…”
Section: Thixotropy—the Most Evident Reflection Of Structure Transfor...mentioning
confidence: 99%
“…In the literature, the subject of hysteresis in viscoelastic materials has been studied in detail both experimentally and theoretically. On an independent but related note, it has been well established that thixotropy, which concerns increase in viscosity under no flow or weak flow conditions and decrease in viscosity under strong flow conditions, shows many behavioural similarities with viscoelasticity [1][2][3][4]. In particular, thixotropic materials also show hysteresis in cyclic shear rate sweep experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the area enclosed by a hysteresis loop as a function of step time in a stepwise down-up ramp has been proposed to show some unique features for a thixotropic material. In our earlier study [4], we assessed four different experimental protocols that have been proposed to distinguish thixotropy and viscoelasticity. We found that stress relaxation and/or creep experiments at different waiting times lead to unique signatures for thixotropic vis-a-vis viscoelastic materials.…”
Section: Introductionmentioning
confidence: 99%